2010
DOI: 10.1002/mds.23314
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 G2019S mutations are associated with an increased cancer risk in Parkinson disease

Abstract: Leucine rich repeat kinase (LRRK2) G2019S mutations are presumed to cause PD through a toxic gain of function of the protein kinase. Small molecule kinase inhibitors have been developed for the treatment of certain cancers, and some antioncogenic agents such as sunitinib, may nonspecifically inhibit LRRK2. Few studies, however, have assessed cancer risk in LRRK2 mutation carriers. To explore this risk, we evaluated records of Ashkenazi Jewish (AJ) PD patients participating in genetic research. Charts were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 36 publications
3
58
2
Order By: Relevance
“…Recently, LRRK2 mutations have been found to be an important risk factor for sporadic and familial PD [24,25]. It has been shown that PD patients with LRRK2 mutations have a different profile of malignancy compared with non-carriers of LRRK2 gene mutations [26,27]. Mutation carriers had a particularly increased risk of breast cancer in both studies, and might explain part of the increased rate in breast cancer in PD patients that we and others find [2,3].…”
Section: Interpretation and Implicationsmentioning
confidence: 55%
“…Recently, LRRK2 mutations have been found to be an important risk factor for sporadic and familial PD [24,25]. It has been shown that PD patients with LRRK2 mutations have a different profile of malignancy compared with non-carriers of LRRK2 gene mutations [26,27]. Mutation carriers had a particularly increased risk of breast cancer in both studies, and might explain part of the increased rate in breast cancer in PD patients that we and others find [2,3].…”
Section: Interpretation and Implicationsmentioning
confidence: 55%
“…Sinai Beth Israel Medical Center, New York). Detailed descriptions about study participants, data collection, LRRK2 genotyping and cancer outcomes for three of the centers have been published 19,20,22,23 and are summarized for all five centers in the eTable in the Supplement. Briefly, at all centers, PD patients were queried regarding demographic and lifestyle factors as well as, personal and family history of PD and other diseases, including self-reported cancer, type of cancer, and age at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The PINK1 and LRRK2 somatic mutations identified in cancer were all heterozygous and their pathological effect remains to be determined. The prevalence of LRRK2 G2019S (the most common genetic determinant of PD) is not increased in patients with melanoma [7], [54], but a recent study showed an almost 3-fold increased risk of non-skin cancers in LRRK2 G2019S mutation carriers [55]. Moreover, of the 18 known mutation carriers of a large family with LRRK2 R1441C parkinsonism, four had colon cancer [56].…”
Section: Proven Genetic Factors Implicated In Neurodegeneration and Pmentioning
confidence: 99%